The Role of The Head of Madrasah in Increasing The Quality of Education at MIN 3 Jembrana Bali - Supriyadi, Supriyadi (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
The head of the Madrasah as the top management has the authority and responsibility to the school he leads. To improve the quality and quality of the Madrasah in achieving maximum results, the head of the Madrasah must be competent, especially in related fields. The urgency of this study is to improve the quality of education, researchers use a qualitative descriptive approach. Informants taken in this study are the head of the madrasah, teachers, and students. Data collection techniques using observation, interviews, and documentation. While data analysis is done systematically starting from data reduction, data presentation, and verification or closing. The final results obtained from this study include: First, the role of the head of the Madrasah in MIN 3 Jembrana includes: educators, managers, administrators, mentors, leaders, innovators, and motivators commonly abbreviated as EMASLIM. Second, the quality of education in MIN 3 Jembrana is very potential, proven MIN 3 Jembrana is very potential evidenced by the number of academic and non-academic achievements both at the provincial and national level so that it can get the title of pilot project Min achievements in Jembrana Regency, and Third, The Role of the head of Madrasah in improving the quality of, harmonious and balanced.